Development of visual control in stepping down. - Cowie, D; Atkinson, J; Braddick, O (2010)
Stepping down at a change of height is a fundamental part of human locomotion. At a novel step, this requires the transformation of visual information about a depth change into a stepping movement of appropriate size. However, little is known about this process or its development. We studied adults, 3- and 4-year-old children stepping down a single stair of variable height. We assessed how well stepping down was scaled to stair height using several kinematic measures. Of these, 'kneedrop' and 'toedrop' describe how far the leg has descended by the time it begins to 'swing in' in preparation for landing; and 'toeheight (speedpeak)' describes where the toe begins to decelerate. If visually controlled, their values should scale to the height of the stair. Under normal visual conditions, children scaled these movements to stair height as well as adults. In a second condition, participants closed their eyes just before stepping down to remove visual feedback during the step. Adults' steps were barely affected. For 4-year olds, only toeheight (speedpeak) decreased. For 3-year olds, both toedrop and toeheight (speedpeak) scaled less well to stair height than normal. The results suggest that visuomotor processes for fine-tuned stepping control develop remarkably early, but are initially dependent on visual feedback.